Valentin and his Wild Brother in European Literature: How French is a Medieval French Romance? - Lydia Zeldenrust; Sofia Lodén (Interfaces: A Journal of Medieval European Literatures, 2022)
The medieval romance about the two brothers Valentin and Orson (also known as Nameless) crossed various linguistic and cultural borders in the European Middle Ages and beyond. It is said to have originated in a Francophone context, but the French origin, which is believed to be a chanson de geste, has not been preserved – the earliest surviving sources are three Middle Dutch fragments. The different versions of the tale are generally divided into two strands: the first covers versions in Middle Dutch, Middle Low German, Middle High German, and Old Swedish, and the second includes versions in French, English, German, Dutch, Italian, Icelandic, and Yiddish. In this article, we give an up-to-date overview of the two strands and raise the question whether Valentin should be considered as a primarily French tradition. We argue that Valentin cannot be understood only in a monolingual or national context, and that a linear model of transmission does not do justice to the complexity of this tradition. We consider what it means to approach Valentin as a shared European narrative, how each version places itself in this larger tradition, and what insight this approach can give us into the tension as well as fruitful co-existence between local and supralocal. By putting the different versions of the tale in dialogue and paying attention to the places and social networks along which they travelled, the article presents a new way of understanding a literary tradition that once enthralled audiences from Flanders to Silesia, and from Venice to Sweden.